Development of Infrared Transmitter Using Vertical Cavity Surface Emitting Laser - Ayatollahi, Fatima Lina (2004)
Developing good IR transmitter shall consider its complexity and type of emitter. Light emitting diode (LED) which is the most commonly used as an emitter is challenged by emerging technology called vertical cavity surface emitting laser (VCSEL). However, the use of VCSEL for infrared signaling has not been reported before. VCSEL is claimed to be easier and more efficient than LED. This research is focusing on development of an infrared transmitter using vertical cavity surface emitting laser (VCSEL) instead of LED. Several design options, which are based on simple gates, MAXIM chips and microprocessor, were explored. Finally, test and analysis were carried out to evaluate the suitability of VCSEL as an infrared transmitter. By comparing the output power of VCSEL and LED; it was obtained that VCSEL can provide efficient power utilization